Validity Test of Motion Graphics Media as A Wide Area Network Learning Media - Panyahuti Panyahuti (Jurnal Teknologi Informasi dan Pendidikan, 2022)
The world of education currently uses many benefits in the form of technology such as computer equipment to assist the process of delivering material. One of them is motion graphics video. The aims of this study are to: (1) Determine the validity of motion graphics video as a learning medium for Wide Area Network materials. (2) Knowing the practicality of video motion graphics as a learning medium in Wide Area Network materials. This type of research is Research and Development (R&D) with a Four D (4D) approach model consisting of Define, Design, Develop, and Disseminate. From the results of the study it can be said that (1) video motion graphics on Wide Area Network materials. that have been developed meet the criteria. The data from the video motion graphics validity test results show the aiken'V value in the expert test results obtained an average media validity in the display aspect of 0.807 in the valid category, the average media validity value in the format aspect media of 0.83 in the valid category, the average validity of the material on the aspect of media presentation is 0.817 in the valid category. The results of the development of motion graphic videos as a whole have been suitable for use or valid as learning media.